CARA AGRIBISNIS MENGATASI KELEMAHAN PRODUKSI DAN MENINGKATKAN PENDAPATAN PETANI - Basir Paly (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2011)
Agriculture yield by farmer at conventional farmer generally own characteristic and nature of permanent upon which row material. Big volume and easy to destroy the ( bulkya and perishable), quality and vary Seasonally ( Long Seasonal). Periode time between gultivation phase with the cropping. Some farmer also difficulties to respon price change which became by the seasonal period explained previously. Farmer difficulty to respon price change through and passing Cobweb-Theorema. So agribisnis give the advantage to solves through Sinergisitas systems, Market Oriented usualt called maximum profite oriented. Keyword:Agribisnis, characteristic, produce, earnings